High-thixotropy low-thermal-resistance super-long-life heat-conducting silicone grease and preparation method thereof
By using micron-scale AlCe microspheres, AlN nanometer microspheres and other constituent materials in thermal grease, and through the compatibility of silicone oils with different branching degrees and end groups, the problems of insufficient deformation and aging resistance of thermal grease are solved, and the thermal conductivity effect with high thixotropy, low thermal resistance and ultra-long life are achieved.
Patent Information
- Application Number
- CN202411927000.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing thermal grease is prone to deformation and has insufficient aging resistance during use, resulting in a degradation of thermal conductivity and cannot meet the heat dissipation needs of high-power electronic components.
A high-thixotropic low thermal resistance ultra-long life thermal conductivity grease is used, and its composition includes micron-scale AlCe microspheres, AlN nano-microspheres, acrylonitrile-butadiene-styrene nanoplastic microspheres, vinyl-terminated silicone oil, methyl-terminated silicone oil, hydroxy-terminated silicone oil and polyglycerol-10 laurate. Through the compatibility of silicone oils with different branching degrees and end groups, wetting and lubricating properties are improved, and thixotropy and high temperature stability are improved through nano-ABS microspheres.
Thermal silicon grease with high thixotropy, low thermal resistance and ultra-long life is achieved. The thermal resistance change rate is less than 5% after 5000 hours of aging at 150℃, which significantly improves the thermal conductivity and the performance and life of the equipment.
Smart Images

Figure CN119708854A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to a high-thixotropic, low-thermal-resistance, ultra-long-life thermal conductive silicone grease and a preparation method thereof. Background Art
[0002] In today's era of rapid development of electronic technology, electronic devices continue to move towards miniaturization, high integration and high performance. This causes the power density per unit area of electronic components to rise sharply. If the heat cannot be dissipated in time, the electronic components will suffer from serious problems such as performance degradation, shortened lifespan or even failure due to overheating. Therefore, the heat dissipation problem has become a key bottleneck restricting the further development of electronic devices.
[0003] At present, the mainstream heat dissipation method uses a metal heat sink to directly contact the heat source, thereby directing the heat from the heat source to the metal heat sink. However, due to the microscopic unevenness between the surface of the electronic component and the heat sink, the actual contact area between the two usually only accounts for a small part of the theoretical contact area, and there are a large number of air gaps on the contact surface. Air is a poor conductor of heat, which greatly hinders the conduction of heat. In order to solve this problem, thermal conductive silicone grease came into being. It is a highly thermally conductive insulating silicone material that can fill these tiny air gaps. With its good fluidity and thermal conductivity, it forms a tighter and lower thermal resistance heat conduction channel between the heat source and the heat sink, thereby significantly improving the heat dissipation efficiency and ensuring the stable and reliable operation of electronic equipment. However, the thermal conductivity of traditional thermal conductive silicone grease is difficult to break through, and the thermal resistance remains high, making it increasingly unable to meet the heat dissipation needs of high-power electronic components. In addition, the current thermal grease products have the following problems that need to be solved: (1) The silicone grease itself has no fixed shape and is prone to flow, overflow or deform due to external forces during use, affecting its effective filling and heat conduction effect between the heating element and the heat dissipation component, especially when the device is vibrated or tilted. (2) In a long-term high temperature environment, it is easy to dry, harden, and age, resulting in a decrease in thermal conductivity, which greatly reduces the heat dissipation effect of the device and further affects the performance and life of the device; and in the long-term use process, the migration, decomposition, and volatilization of the liquid in the silicone grease will also further increase the thermal resistance and reduce the heat transfer effect. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a thermally conductive silicone grease with high thixotropy, low thermal resistance and ultra-long life in view of the deficiencies in the prior art, so as to solve the problems of easy deformation and insufficient aging resistance of the existing silicone grease itself, and further improve its thermal conductivity.
[0005] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows: A high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease, characterized in that it comprises the following components in percentage by mass: Micron-sized AlCe microspheres 65~87wt%; AlN nanospheres 6~26wt%; Acrylonitrile-butadiene-styrene nanoplastic microspheres 2~4wt%; Vinyl terminated silicone oil 2~2.5wt%; Methyl terminated silicone oil 0.5~0.75wt%; Hydroxyl terminated silicone oil 0.5~0.75wt%; Polyglycerol-10 laurate 1~2wt%.
[0006] Furthermore, in the micron-sized AlCe microspheres, the mass ratio of Ce element to Al element is 0.02-0.025, preferably 0.022.
[0007] Furthermore, the micron-sized AlCe microspheres include AlCe microspheres with a particle size of 4 to 6 micrometers, AlCe microspheres with a particle size of 1 to 3 micrometers, and AlCe microspheres with a particle size of 0.3 to 0.5 micrometers.
[0008] Preferably, the AlCe microspheres with a particle size of 4 to 6 microns account for 40 wt% to 50 wt% of the total thermal conductive silicone grease. AlCe microspheres with a particle size of 1 to 3 microns account for 20wt% to 30wt% of the total thermal grease mass percentage. The AlCe microspheres with a particle size of 0.3 to 0.5 microns account for 5wt% to 7wt% of the total thermal conductive silicone grease.
[0009] Furthermore, the particle size of the AlN nanospheres is 100-300 nanometers.
[0010] Furthermore, the particle size of the acrylonitrile-butadiene-styrene nanoplastic microspheres is 50 to 100 nanometers.
[0011] Furthermore, the dynamic viscosity of the vinyl-terminated silicone oil is 150 cst and the branching factor is 0.3-0.5.
[0012] Furthermore, the methyl-terminated silicone oil has a dynamic viscosity of 100 cst and a branching factor of 0.7-0.9.
[0013] Furthermore, the hydroxyl-terminated silicone oil has a dynamic viscosity of 300 cst and a branching factor of 0.4-0.6.
[0014] Furthermore, the present invention also claims a method for preparing the above-mentioned high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease, comprising the following steps: (1) Mixing vinyl-terminated silicone oil and methyl-terminated silicone oil, stirring at a speed of 300-500 rpm, and continuously stirring for 10-30 minutes to obtain a first mixed solution; (2) Mixing the hydroxyl-terminated silicone oil and polyglycerol-10 laurate, stirring at a speed of 300-500 rpm, and continuously stirring for 10-30 minutes to obtain a second mixed solution; (3) adding acrylonitrile-butadiene-styrene plastic microspheres to the second mixed solution obtained in step (2), heating to 60-80° C., 300-500 rpm, stirring continuously for 1-3 hours, and cooling to room temperature to obtain a first mixture; (4) adding the first mixed solution obtained in step (1) to the first mixture obtained in step (3), and stirring at a speed of 300 to 500 rpm for 20 to 40 minutes to obtain a second mixture; (5) adding micron-sized AlCe microspheres and AlN nano-microspheres to cyclohexane in proportion, and stirring the mixture in a sealed state for 1 to 3 hours at a stirring speed of 100 to 300 rpm to obtain a third mixture, wherein the mass ratio of the sum of the microspheres to the mass of cyclohexane is 3 to 4:1; (6) Add the second mixture to the third mixture obtained in step (5) in proportion, seal and stir at a speed of 700-900 rpm for 5-15 minutes to obtain a fourth mixture; (7) opening the lid of the container containing the fourth mixture, removing the sealing state, raising the temperature to 40-50° C., evacuating the pressure to below 2 kPa, and maintaining the pressure for 2-4 hours to remove the cyclohexane, and cooling to room temperature to obtain a fifth mixture; (8) The fifth mixture obtained in step (7) is subjected to vacuum degassing at room temperature with a stirring speed of 1000-1200 rpm, a vacuum degree of less than 1 kPa, and a degassing time of 10-20 minutes to obtain the fifth mixture. Beneficial Effects
[0015] (1) The present invention obtains a compound silicone oil with higher wettability and lubricity by mixing silicone oils with different branching degrees and different end groups, thereby reducing the friction between powders and increasing the powder filling rate; on the other hand, by mixing the silicone oils described in the present invention, the entanglement of the molecular chains between silicone oils with different branching degrees and different end groups and the interaction between the end groups can be used to obtain a better shape retention ability at high temperatures. By adding nano ABS microsphere powder, on the one hand, the thixotropy of the material is improved, and on the other hand, the high temperature stability and shape retention ability of the thermal conductive silicone grease are improved by utilizing the characteristics of ABS softening and swelling at high temperatures; by adding Ce elements to the Al matrix, due to the low electronegativity of Ce, more metal is provided to Al, increasing the electron density of the conduction band; at the same time, the addition of Ce can modulate the electronic structure of Al, so that the s-band and p-band of Al are further expanded, and the mobility of the conduction band electrons is improved; the above two effects make AlCe have a higher thermal conductivity than pure Al.
[0016] (2) The present invention provides a preparation process through the selection of components and ratios and strict control of parameters, which realizes the controllable preparation of high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease. The obtained thermal conductive silicone grease has a thixotropic index greater than 15 and a thermal resistance (40psi) less than 0.025 cm 2 .K / W; 150 ℃ After 1000 hours of high temperature aging, the thermal resistance (40psi) change rate is less than 3%, 150 ℃ After 5000 hours of high temperature aging, the change rate of thermal resistance (40psi) is less than 5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0018] Figure 1 Example 1 thermal conductive silicone grease at 150 o C changes in thermal resistance data over time. DETAILED DESCRIPTION
[0019] The present invention can be better understood with reference to the following examples.
[0020] In the following examples, AlCe0.022 microspheres represent microspheres in which the mass ratio of Ce element to Al element is 0.022. AlCe0.023 microspheres represent microspheres in which the mass ratio of Ce element to Al element is 0.023. AlCe0.025 microspheres represent microspheres in which the mass ratio of Ce element to Al element is 0.025. Example 1
[0021] A high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease: the components include 40wt% of AlCe0.022 microspheres with a particle size of 4-5 microns, 20wt% of AlCe0.022 microspheres with a particle size of 1-2 microns, 5wt% of AlCe0.022 microspheres with a particle size of 0.3-0.4 microns, 26wt% of AlN microspheres with a particle size of 100-200 nanometers, 4wt% of acrylonitrile-butadiene-styrene (ABS) plastic microspheres with a particle size of 50-75 nanometers, 2wt% of vinyl-terminated silicone oil with a branching factor g of 0.3 and a dynamic viscosity of 150 cst, 0.5wt% of methyl-terminated silicone oil with a branching factor g of 0.7 and a dynamic viscosity of 100 cst, 0.5wt% of hydroxyl-terminated silicone oil with a branching factor g of 0.4 and a dynamic viscosity of 300 cst, and 2wt% of polyglycerol-10 laurate.
[0022] Prepared by the following steps: (1) vinyl-terminated silicone oil with a dynamic viscosity of 150 cst and a branching factor g of 0.3 and methyl-terminated silicone oil with a dynamic viscosity of 100 cst and a branching factor g of 0.7 were mixed in proportion, stirred at a speed of 300 rpm, and stirred for 10 minutes to obtain a first mixed solution; (2) a hydroxyl-terminated silicone oil with a dynamic viscosity of 300 cst and a branching factor g of 0.4 and polyglycerol-10 laurate were mixed in proportion, stirred at a speed of 300 rpm, and stirred for 10 minutes to obtain a second mixed solution; (3) adding acrylonitrile-butadiene-styrene (ABS) plastic microspheres with a particle size of 50 to 75 nanometers to the second mixed solution obtained in step (2), heating to 60° C., 300 rpm, stirring continuously for 1 hour, and cooling to room temperature to obtain a first mixture; (4) adding the first mixed solution obtained in step (1) to the first mixture obtained in step (3), and stirring at a speed of 300 rpm for 20 minutes to obtain a second mixture; (5) Adding AlCe0.022 microspheres with a particle size of 4-5 μm, AlCe0.022 microspheres with a particle size of 1-2 μm, AlCe0.022 microspheres with a particle size of 0.3-0.4 μm, and AlN microspheres with a particle size of 100-200 nm to cyclohexane in proportion, sealing the mixture, and stirring for 1 hour at a stirring speed of 100 rpm to obtain a third mixture; wherein the mass ratio of the sum of the microspheres to the mass of cyclohexane is 3:1; (6) Add the second mixture to the third mixture obtained in step (5) in proportion, cover and seal, and stir at a speed of 700 rpm for 5 minutes to obtain a fourth mixture; (7) opening the lid of the container containing the fourth mixture, removing the sealing state, heating it to 40° C., evacuating the pressure to 2 kPa, and maintaining the pressure for 2 hours, and cooling it to room temperature to obtain a fifth mixture; (8) The fifth mixture obtained in step (7) is placed in a planetary vacuum stirring degassing machine for vacuum degassing at room temperature, with a stirring speed of 1000 rpm, a vacuum degree of 1 kPa, and a degassing time of 10 minutes, thereby obtaining a high thixotropic, low thermal resistance, and ultra-long life thermal conductive silicone grease.
[0023] After testing, under 25℃, the thixotropic index of the thermal conductive silicone grease (7# rotor, η 10rpm / η 1rpm ) is 15.6; thermal resistance (40psi) is 0.024 cm 2 .K / W; after aging at 150℃ for 1000 hours, the change rate of thermal resistance (40psi) is 2.9%, and after aging at 150℃ for 5000 hours, the change rate of thermal resistance (40psi) is 5.0%. Example 2
[0024] A high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease: the components include 50wt% of AlCe0.025 microspheres with a particle size of 5-6 microns, 30wt% of AlCe0.025 microspheres with a particle size of 2-3 microns, 7wt% of AlCe0.025 microspheres with a particle size of 0.4-0.5 microns, 6wt% of AlN microspheres with a particle size of 200-300 nanometers, 2wt% of acrylonitrile-butadiene-styrene (ABS) plastic microspheres with a particle size of 75-100 nanometers, 2.5wt% of vinyl-terminated silicone oil with a branching factor g of 0.5 and a dynamic viscosity of 150cst, 0.75wt% of methyl-terminated silicone oil with a branching factor g of 0.9 and a dynamic viscosity of 100cst, 0.75wt% of hydroxyl-terminated silicone oil with a branching factor g of 0.6 and a dynamic viscosity of 300cst, and 1wt% of polyglycerol-10 laurate Prepared by the following steps: (1) vinyl-terminated silicone oil with a dynamic viscosity of 150 cst and a branching factor g of 0.5 and methyl-terminated silicone oil with a dynamic viscosity of 100 cst and a branching factor g of 0.9 were mixed in proportion, stirred at a speed of 500 rpm, and stirred for 30 minutes to obtain a first mixed solution; (2) a hydroxyl-terminated silicone oil with a dynamic viscosity of 300 cst and a branching factor g of 0.6 and polyglycerol-10 laurate were mixed in proportion, stirred at a speed of 500 rpm, and stirred for 30 minutes to obtain a second mixed solution; (3) Adding acrylonitrile-butadiene-styrene (ABS) plastic microspheres with a particle size of 75 to 100 nanometers to the second mixed solution obtained in step (2), heating to 80° C., 500 rpm, stirring continuously for 3 hours, and cooling to room temperature to obtain a first mixture; (4) adding the first mixed solution obtained in step (1) to the first mixture obtained in step (3), and stirring at a speed of 500 rpm for 40 minutes to obtain a second mixture; (5) Adding AlCe0.025 microspheres with a particle size of 5 to 6 μm, AlCe0.022 microspheres with a particle size of 2 to 3 μm, AlCe0.025 microspheres with a particle size of 0.4 to 0.5 μm, and AlN microspheres with a particle size of 200 to 300 nm to cyclohexane in proportion, sealing the mixture, and stirring for 3 hours at a stirring speed of 300 rpm to obtain a third mixture; wherein the mass ratio of the sum of the microspheres to the mass of cyclohexane is 4:1; (6) Add the second mixture to the third mixture obtained in step (5) in proportion, cover and seal, and stir at a speed of 900 rpm for 15 minutes to obtain a fourth mixture; (7) opening the lid of the container containing the fourth mixture, removing the sealing state, heating it to 50° C., evacuating the pressure to 2 kPa, and maintaining the pressure for 4 hours, and cooling it to room temperature to obtain a fifth mixture; (8) The fifth mixture obtained in step (7) is placed in a planetary vacuum stirring degassing machine for vacuum degassing at room temperature, with a stirring speed of 1200 rpm, a vacuum degree of 1 kPa, and a degassing time of 20 minutes, thereby obtaining a high thixotropic, low thermal resistance, and ultra-long life thermal conductive silicone grease.
[0025] After testing, under 25℃, the thixotropic index of the thermal conductive silicone grease (7# rotor, η 10rpm / η 1rpm ) is 17.7; thermal resistance (40psi) is 0.016cm 2 .K / W, the change rate of thermal resistance (40psi) after aging at 150℃ for 1000 hours is 1.5%, and the change rate of thermal resistance (40psi) after aging at 150℃ for 5000 hours is 2.9%. Example 3
[0026] A high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease: the components include 45wt% AlCe0.023 microspheres with a particle size of 4.5-5.5 microns, 25wt% AlCe0.023 microspheres with a particle size of 1.5-2.5 microns, 6wt% AlCe0.023 microspheres with a particle size of 0.35-0.45 microns, 16wt% AlN microspheres with a particle size of 150-250 nanometers, 3wt% acrylonitrile-butadiene-styrene (ABS) plastic microspheres with a particle size of 65-90 nanometers, 2.25wt% vinyl-terminated silicone oil with a branching factor g of 0.4 and a dynamic viscosity of 150cst, 0.6wt% methyl-terminated silicone oil with a branching factor g of 0.8 and a dynamic viscosity of 100cst, 0.65wt% hydroxyl-terminated silicone oil with a branching factor g of 0.5 and a dynamic viscosity of 300cst, and 1.5wt% polyglycerol-10 laurate Prepared by the following steps: (1) vinyl-terminated silicone oil with a dynamic viscosity of 150 cst and a branching factor g of 0.4 and methyl-terminated silicone oil with a dynamic viscosity of 100 cst and a branching factor g of 0.8 were mixed in proportion, stirred at a speed of 400 rpm, and stirred for 20 minutes to obtain a first mixed solution; (2) a hydroxyl-terminated silicone oil with a dynamic viscosity of 300 cst and a branching factor g of 0.5 and polyglycerol-10 laurate were mixed in proportion, stirred at a speed of 400 rpm, and stirred for 20 minutes to obtain a second mixed solution; (3) adding acrylonitrile-butadiene-styrene (ABS) plastic microspheres with a particle size of 65 to 90 nanometers to the second mixed solution obtained in step (2), heating to 70° C., 400 rpm, stirring continuously for 2 hours, and cooling to room temperature to obtain a first mixture; (4) adding the first mixed solution obtained in step (1) to the first mixture obtained in step (3), and stirring at a speed of 400 rpm for 30 minutes to obtain a second mixture; (5) Adding AlCe0.023 microspheres with a particle size of 4.5-5.5 μm, AlCe0.023 microspheres with a particle size of 1.5-2.5 μm, AlCe0.023 microspheres with a particle size of 0.35-0.45 μm, and AlN microspheres with a particle size of 150-250 nm to cyclohexane in proportion, sealing the mixture with a lid, and stirring for 2 hours at a stirring speed of 200 rpm to obtain a third mixture; wherein the mass ratio of the sum of the masses of the microspheres to the mass of cyclohexane is 3.5:1; (6) adding the second mixture in proportion to the third mixture obtained in step (5), sealing the mixture with a cover, and stirring at a speed of 800 rpm for 10 minutes to obtain a fourth mixture; (7) opening the lid of the container containing the fourth mixture, removing the sealing state, heating it to 45° C., evacuating the pressure to 2 kPa, and maintaining the pressure for 3 hours, and cooling it to room temperature to obtain a fifth mixture; (8) The fifth mixture obtained in step (7) is placed in a planetary vacuum stirring degassing machine for vacuum degassing at room temperature, with a stirring speed of 1100 rpm, a vacuum degree of 1 kPa, and a degassing time of 15 minutes, thereby obtaining a high thixotropic, low thermal resistance, and ultra-long life thermal conductive silicone grease.
[0027] After testing, under 25℃, the thixotropic index of the thermal conductive silicone grease (7# rotor, η 10rpm / η 1rpm ) is 16.4; thermal resistance (40psi) is 0.019 cm 2 .K / W, the change rate of thermal resistance (40psi) is 2.1% after aging at 150℃ for 1000 hours, and the change rate of thermal resistance (40psi) is less than 3.3% after aging at 150℃ for 5000 hours. Comparative Example 1
[0028] Use commercially available Dow TC5888 thermal grease.
[0029] After testing, under 25℃, the thixotropic index of the thermal conductive silicone grease (7# rotor, η 10rpm / η 1rpm ) is 8.9; thermal resistance (40psi) is 0.044cm 2 .K / W, the change rate of thermal resistance (40psi) after aging at 150℃ for 1000 hours is 5.2%, and the change rate of thermal resistance (40psi) after aging at 150℃ for 5000 hours is 6.7%. Comparative Example 2
[0030] Commercially available Shin-Etsu 7921 thermal grease is used.
[0031] After testing, under 25℃, the thixotropic index of the thermal conductive silicone grease (7# rotor, η 10rpm / η 1rpm ) is 7.7; thermal resistance (40psi) is 0.042cm 2 .K / W, the change rate of thermal resistance (40psi) after aging at 150℃ for 1000 hours is 6.1%, and the change rate of thermal resistance (40psi) after aging at 150℃ for 5000 hours is 8.9%. Comparative Example 3
[0032] The difference between this comparative example and Example 1 is that the micron-sized AlCe microspheres are replaced with micron-sized Al microspheres, and the Ce element is not added to the Al matrix.
[0033] The preparation method is the same as that of Example 1. After testing, the thixotropic index of the thermal conductive silicone grease (7# rotor, η 10rpm / η 1rpm ) is 11.1; thermal resistance (40psi) is 0.041 cm 2 .K / W; after aging at 150℃ for 1000 hours, the change rate of thermal resistance (40psi) is 4.7%, and after aging at 150℃ for 5000 hours, the change rate of thermal resistance (40psi) is 7.7%.
[0034] The present invention provides a high thixotropic, low thermal resistance, ultra-long life thermal conductive silicone grease and its preparation method. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made, and these improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease, characterized in that: It includes the following components in percentage by mass: Micron-sized AlCe microspheres 65~87wt%; AlN nanospheres 6~26wt%; Acrylonitrile-butadiene-styrene nanoplastic microspheres 2~4wt%; Vinyl terminated silicone oil 2~2.5wt%; Methyl terminated silicone oil 0.5~0.75wt%; Hydroxyl terminated silicone oil 0.5~0.75wt%; Polyglycerol-10 laurate 1~2wt%.
2. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: In the micron-sized AlCe microspheres, the mass ratio of Ce element to Al element is 0.02-0.
025.
3. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The micron-sized AlCe microspheres include AlCe microspheres with a particle size of 4 to 6 micrometers, AlCe microspheres with a particle size of 1 to 3 micrometers, and AlCe microspheres with a particle size of 0.3 to 0.5 micrometers.
4. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 3, characterized in that: The mass percentage of the AlCe microspheres with a particle size of 4 to 6 microns is 40wt% to 50wt%, the mass percentage of the AlCe microspheres with a particle size of 1 to 3 microns is 20wt% to 30wt%, and the mass percentage of the AlCe microspheres with a particle size of 0.3 to 0.5 microns is 5wt% to 7wt%.
5. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The particle size of the AlN nanospheres is 100-300 nanometers.
6. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The particle size of the acrylonitrile-butadiene-styrene nano plastic microspheres is 50-100 nanometers.
7. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The dynamic viscosity of the vinyl-terminated silicone oil is 150 cst, and the branching factor is 0.3-0.
5.
8. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The methyl-terminated silicone oil has a dynamic viscosity of 100 cst and a branching factor of 0.7-0.
9.
9. The high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The hydroxyl-terminated silicone oil has a dynamic viscosity of 300 cst and a branching factor of 0.4-0.
6.
10. The method for preparing the high thixotropic, low thermal resistance and ultra-long life thermal conductive silicone grease according to claim 1, characterized in that: The steps include: (1) Mixing vinyl-terminated silicone oil and methyl-terminated silicone oil, stirring at a speed of 300-500 rpm, and continuously stirring for 10-30 minutes to obtain a first mixed solution; (2) Mixing the hydroxyl-terminated silicone oil and polyglycerol-10 laurate, stirring at a speed of 300-500 rpm, and continuously stirring for 10-30 minutes to obtain a second mixed solution; (3) adding acrylonitrile-butadiene-styrene plastic microspheres to the second mixed solution obtained in step (2), heating to 60-80° C., 300-500 rpm, stirring continuously for 1-3 hours, and cooling to room temperature to obtain a first mixture; (4) adding the first mixed solution obtained in step (1) to the first mixture obtained in step (3), and stirring at a speed of 300 to 500 rpm for 20 to 40 minutes to obtain a second mixture; (5) adding micron-sized AlCe microspheres and AlN nano-microspheres to cyclohexane in proportion, and stirring the mixture in a sealed state for 1 to 3 hours at a stirring speed of 100 to 300 rpm to obtain a third mixture, wherein the mass ratio of the sum of the microspheres to the mass of cyclohexane is 3 to 4:1; (6) Add the second mixture to the third mixture obtained in step (5) in proportion, seal and stir at a speed of 700-900 rpm for 5-15 minutes to obtain a fourth mixture; (7) opening the lid of the container containing the fourth mixture, removing the sealing state, raising the temperature to 40-50° C., evacuating the pressure to below 2 kPa, and maintaining the pressure for 2-4 hours to remove the cyclohexane, and cooling to room temperature to obtain a fifth mixture; (8) The fifth mixture obtained in step (7) is subjected to vacuum degassing at room temperature with a stirring speed of 1000-1200 rpm, a vacuum degree of less than 1 kPa, and a degassing time of 10-20 minutes to obtain the fifth mixture.
Citation Information
Patent Citations
Rare-earth-based insulating material and preparation process thereof
CN114940804A
Two-component heat-conducting gel and preparation method thereof
CN115838535A
Vinyl-terminated branched structure polysiloxane as well as preparation method and application thereof
CN118085289A
Fluorine-containing organopolysiloxane composition and method for producing the same
JP2011184527A
Organic silicone resin aluminum base copper clad laminate and preparation method thereof
WO2017028383A1